The impact of content marketing on attitudes and purchase intentions of online shoppers : the case videos & tutorials and user-generated content - Milhinhos, Patrícia Raquel Vasques (2015)
This thesis was written as part of a Double-Degree Masters program in Management, with focus in Marketing. Aligned with the nature of the degree, this study aims to be a useful tool for managers and marketers, which conduct business online. This thesis is a study of Content Marketing in the content of online commercial product pages. Its aim is to understand how to use content marketing to drive conversion, by understanding consumer attitudes and purchase intention towards content. A in-depth study of existing theories and exploratory primary research was developed in other to attain these objectives. Business-to-consumer electronic commerce (B2C e-commerce) has provided consumers and online retailers with a more effective medium to perform online transactions through commercial websites. Although consumers have realized that the benefits of online shopping; such as time saving, minimizing effort, convenience, broader selection, and wider access to information, they are still greatly unwilling to shop online. Consumers shop essentially for two motives, to meet experiential (fun) or goal-oriented (efficiency) needs (Wolfinbarger & Gilly, 2001). The information provided by content marketing seeks to focus on consumers need for information and entertainment, instead of focusing on the brand. Thus, it is expected that the type of content format will have different effects on the attitudes and purchase intention on the online shopper, depending on the online shopping purpose. Concretely, a goal-oriented shopper should find user generated content (UGC) to be more valuable content formats, since they decrease the amount of search effort. While on the other hand, videos & tutorials (VT) might be perceived as more valuable for a consumer looking to spend time and being entertained through online shopping. The exploratory research was characterized by a survey experiment with online consumers. Participants were exposed to stimuli of content marketing tested according to their attitudes and purchase intention. The focus was to understand the impact of two different content marketing tactics—User-generated content and Videos & Tutorials—on attitudes and purchase intentions and how they interact with content complexity. The results indicate that content marketing in commercial product pages is relevant in driving consumer attitudes and purchase intentions. Consumers are not motivated by a specific content marketing tactic, unless that content has a certain level of complexity. In that case, Ur-Generated Content becomes a relevant tactic in product pages, however VT is not.